Acute kidney injury in patients with acute coronary syndrome undergoing invasive management treated with bivalirudin vs. unfractionated heparin: insights from the MATRIX trial. Issue 10 (7th September 2021) - Landi, Antonio; Branca, Mattia; Andò, Giuseppe; Russo, Filippo; Frigoli, Enrico; Gargiulo, Giuseppe; Briguori, Carlo; Vranckx, Pascal; Leonardi, Sergio; Gragnano, Felice; Calabrò, Paolo; Campo, Gianluca; et al.
Abstract: Aims: Acute kidney injury (AKI) is a critical complication among patients with acute coronary syndrome (ACS) undergoing invasive management. The value of adjunctive antithrombotic strategies, such as bivalirudin or unfractionated heparin (UFH) on the risk of AKI is unclear. Methods and results: Among 7213 patients enrolled in the MATRIX-Antithrombin and Treatment Duration study, 128 subjects were excluded due to incomplete information on serum creatinine (sCr) or end-stage renal disease on dialysis treatment. The primary endpoint was AKI defined as an absolute (>0.5 mg/dL) or a relative (>25%) increase in sCr. AKI occurred in 601 patients (16.9%) treated with bivalirudin and 616 patients (17.4%) treated with UFH [odds ratio (OR): 0.97; 95% confidence interval (CI): 0.85–1.09; P  = 0.58]. A >25% sCr increase was observed in 597 patients (16.8%) with bivalirudin and 616 patients (17.4%) with UFH (OR: 0.96; 95% CI: 0.85–1.08; P  = 0.50), whereas a >0.5 mg/dL absolute sCr increase occurred in 176 patients (5.0%) with bivalirudin vs. 189 patients (5.4%) with UFH (OR: 0.92; 95% CI: 0.75–1.14; P  = 0.46). By implementing the Kidney Disease Improving Global Outcomes (KDIGO) criteria, the risk of AKI was not significantly different between bivalirudin and UFH groups (OR: 0.88; 95% CI: 0.72–1.07; P  = 0.21). Subgroup analyses of the primary endpoint suggested a benefit with bivalirudin in patients randomized to femoral access. Conclusion: Among ACS patients undergoing invasive management, the risk of AKI was not significantly lower with bivalirudin compared with UFH. Trial registration: clinicaltrials.gov NCT01433627. Graphical Abstract: